Downshifting Layer of Europium‐Doped NaGdF4: From the Optimization of the Sol–Gel Process to the Luminescent Properties - Anna Lucia Pellegrino; Francesca Lo Presti; Francesca Loschi; Adolfo Speghini; Graziella Malandrino (Advanced Photonics Research)
The key issue for a wide application of solar energy is the possibility to establish an innovative photovoltaic technology that allows a more efficient energy conversion. In this direction, the use of additional layers in the well‐established silicon‐based modules represents a challenging strategy. In this context, the present work is devoted to the optimization of a downshifting (DS) system made of the NaGdF4 matrix in the form of thin film as a host material for the europium‐luminescent ions. The Eu‐doped NaGdF4 system is fabricated through a sol–gel approach starting from a mixture of Na(hfa)•tetraglyme, Gd(hfa)3•diglyme, and Eu(hfa)3•diglyme in ethanol solution. The operative parameters are finely tuned to pursue the formation of compact and polycrystalline films. Particularly, the annealing treatment, the nature of the substrate, and the doping ion percentage are the key parameters for the reproducible and selective formation of NaGdF4 in the form of the beta (hexagonal) crystal structure with promising luminescent properties. Morphological, structural, and compositional features are deeply studied through field‐emission scanning electron microscopy, X‐ray diffraction analysis, and energy‐dispersive X‐ray analysis, respectively. The luminescence investigations confirm the properties of the Eu‐doped NaGdF4 as DS system.